Temporal beta diversity patterns reveal global change impacts in closed mountain grasslands. (4th March 2023) - Lelli, Chiara; Chiarucci, Alessandro; Tomaselli, Marcello; Di Musciano, Michele; Lasen, Cesare; Poloniato, Gianni; Nascimbene, Juri
Abstract: Global changes are recognized as one of the main drivers of biodiversity changes over time, especially in mountain ecosystems. A key approach to detect and investigate the effect of climate and land use change on these ecosystems is represented by vegetation surveys. In this study, based on the resurvey of historical vegetation data, we assessed temporal beta-diversity patterns within and between subalpine and alpine vegetation types in the Dolomiti Bellunesi National Park. Resurvey was focussed on plots sampled in four main vegetation types: 1 and 2) Mesophytic and xerophytic grasslands on neutral or base-rich soils respectively dominated by Sesleria caerulea and Carex sempervirens and by Sesleria caerulea and Helictotrichon parlatorei ; 3) Acidophytic grasslands dominated by Nardus stricta ; 4) Snowbeds with dominance of dwarf willows ( Salix herbacea or S. retusa ) or Luzula alpinopilosa . Our results revealed a pattern of floristic homogenization in grasslands and snowbeds indicating a decreasing heterogeneity, both within and between different vegetation types that can be associated with different components of global change. The highest temporal beta diversity and floristic homogenization were detected in snowbeds. In general, the magnitude of temporal changes differ between communities, thus claiming for conservation activities that are tailored to each vegetation type.